Rebellion under the Banner of Islam - van Dijk, C. (Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde, 1981)
The Darul Islam rebellion, striving for the establishment of an Islamic State of Indonesia, broke out in several areas since 1949. The author describes each of these Darul Islam rebellions and identifies some of the factors which may help to explain their outbreak and persistence.